Pengaruh Pembiayaan Terhadap Profitabilitas Bank Umum Syariah - Harnum, Mutiara Puspita; Maulidiyah, Musaidatul; Jayanti, Rista Dwi; Septiyanti, Tifanny Tassyah; Canggih, Clarashinta (Jurnal Ekonomika dan Bisnis Islam, 2024)
Islamic banking plays a crucial role in driving economic growth and stability in Indonesia. Islamic banking has shown positive growth, including in BUS, UUS, and BPRS. The market share of Islamic banking has also grown, reaching 6.74% of the national banking sector. However, there are challenges in ensuring that the financing products offered can enhance the bank's profitability while adhering to Islamic values. This study aims to determine the effect of profit sharing financing and non-profit sharing financing both partially and simultaneously on profitability (ROA) at Sharia Commercial Banks. The research method used in this study is quantitative research method with Multiple Linear Regression analysis model. The results showed that partial profit-sharing financing had a negative and significant effect on profitability (ROA), and partial non-profit-sharing financing had a positive and significant effect on profitability (ROA). while simultaneously profit-sharing financing and non-profit-sharing financing affect profitability (ROA). The implications of this study's results suggest that non-profit-sharing financing can be a more profitable alternative for banks in enhancing profitability, allowing them to focus more on developing non-profit-sharing financing products to achieve better economic stability.